HIV self-testing positivity rate and linkage to confirmatory testing and care: a telephone survey in Côte d’Ivoire, Mali, and Senegal - Kra, Arsène Kouassi; Fotso, Arlette Simo; Rouveau, Nicolas; Maheu-Giroux, Mathieu; Boily, Marie-Claude; Silhol, Romain; d’Elbée, Marc; Vautier, Anthony; Larmarange, Joseph (Peer Community Journal)

(untitled)
HIV self-testing (HIVST) empowers individuals to decide when and where to test and with whom to share their results. From 2019 to 2022, the ATLAS program distributed ∼ 400 000 HIVST kits in Côte d’Ivoire, Mali, and Senegal. It prioritised key populations, including female sex workers and men who have sex with men, and encouraged secondary distribution of HIVST to their partners, peers and clients.To preserve the confidential nature of HIVST, use of kits and their results were not systematically tracked. Instead, an anonymous phone survey was carried out in two phases during 2021 to estimate HIVST positivity rates (phase 1) and linkage to confirmatory testing (phase 2). Initially, participants were recruited via leaflets from March to June and completed a sociobehavioural questionnaire. In the second phase (September-October), participants who had reported two lines or who reported a reactive result were recontacted to complete another questionnaire. Of the 2 615 initial participants, 89.7% reported a consistent response between the number of lines on the HIVST and their interpretation of the result (i.e., ‘non-reactive’ for 1 line, ‘reactive’ for 2 lines).Overall positivity rate based on self-interpreted HIVST results was 2.5% considering complete responses, and could have ranged from 2.4% to 9.1% depending on the interpretation of incomplete responses. Using the reported number of lines, this rate was estimated at 4.5% (ranging from 4.4% to 7.2%). Positivity rates were significantly lower only among respondents with higher education. No significant difference was observed by age, key population profile, country or history of HIV testing.The second phase saw 78 out of 126 eligible participants complete the questionnaire. Of the 27 who reported a consistent reactive response in the first phase, 15 (56%, 95%CI: 36 to 74%) underwent confirmatory HIV testing, with 12 (80%) confirmed as HIV-positive, all of whom began antiretroviral treatment.The confirmation rate of HIVST results was fast, with 53% doing so within a week and 91% within three months of self-testing. Two-thirds (65%) went to a general public facility, and one-third to a facility dedicated to key populations.The ATLAS HIVST distribution strategy reached people living with HIV in West Africa. Linkage to confirmatory testing following a reactive HIVST remained relatively low in these first years of HIVST implementation. However, if confirmed HIV-positive, almost all initiated treatment. HIVST constitutes a relevant complementary tool to existing screening services.